"How old do you feel today at work?" Work-related drivers of subjective age in the workplace. Issue 3 (3rd May 2020) - Goecke, Theresa; Kunze, Florian
ABSTRACT: Most Western societies face the challenge of steadily ageing workforces. In recent decades, research on ageing has intensively focused on the subjective age concept to understand the challenges and risks of increasingly ageing workforces. Nevertheless, the subjective age construct is subject to several conceptual uncertainties, namely, regarding its stability and potential work-specific drivers of subjective age. We address these limitations by a) investigating the stability of subjective age in a worker sample, and b) identifying work-specific drivers (e.g., negative work events, positive work events, work stress) of subjective age perceptions. Building on social identity and lifespan theories, we test our conceptual assumptions with an online sample of 168 U.S. employees, applying growth curve modelling in a daily diary study over one workweek. Results indicate that subjective age is a mutable construct and varies between- and within-person in the course of a workweek. We identify positive work events and work stress as between-person drivers and negative work events as a within-person driver of subjective age. We discuss theoretical implications of these findings as well as consequences for practitioners.